Food and Nutrition Consumption of Rural Households in Northern India (Indian Journal of Extension Education, 2022)
Adequate and proper nutritious food is essential for essential for healthy lifestyle and good human health. Thus, promoting nutritious food among rural households is crucial for food and nutritional security. The study on ‘Nutrition Education for Enhancing Nutritional Security and Gender Empowerment’ was carried out for rural households in selected villages of Muzaffarnagar district in western Uttar Pradesh from 2014-15 to 2019-20. The data collected from 120 respondents revealed that more than 60 per cent school children (both boys and girls) and farm women were observed healthy with 61.67 per cent and 63.33 per cent, respectively with BMI score of 18.50 to 24.99 kg/m2. The food consumption pattern of rural households revealed that cent per cent children had a food consumption pattern of three meals per day followed by male adult (80.00%), pregnant women (63.33%). The study also revealed that more than half of the school children (58.34%) and farm women (65.00%) were found in medium level of awareness about food nutrition. The prevalence of underweight and obesity among school children and farm women was observed low.